Improving Students Ability in Writing Essay Through “Free Weekly Writing” Activity - Humaira Humaira; Siti Lamusiah; Isnaini Isnaini; Ilham Ilham (Muhammadiyah University of Mataram, 2019)
Free weekly writing is designed for students to write in every week using free topic based on students’ passion. This action research investigated the effectiveness of implementing free weekly writing in improving students’ writing ability. The participants of this study were 35 students at the VI semester of English Department, FKIP UM-Mataram in academic year 2015-2016. The data were collected by four stages of action research; planning, action, observation, and reflection. The finding of the research proved that almost 83% passed the passing grade. Means that only about 17% students failed to reach the passing grade. There are some factors affected the students’ ability in writing, they were; (a) a writer is forced to read a lot from many sources and having the knowledge, (b) a writer must have well understanding about content and focus of writing, (c) grammatical competence, (d) comprehending the rules of punctuation of in writing, (e) a professional writer must have own characteristic.